2022
DOI: 10.1039/d1cb00251a
|View full text |Cite
|
Sign up to set email alerts
|

6″-Modifed α-GalCer-peptide conjugate vaccine candidates protect against liver-stage malaria

Abstract: Self-adjuvanting vaccines consisting of peptide epitopes conjugated to immune adjuvants are a powerful way of generating antigen-specific immune responses. We previously showed that a Plasmodium-derived peptide conjugated to a rearranged...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Oxime ligation between carbonyl-containing compounds (i.e., aldehydes or ketones) and peptides functionalized with an aminooxy group is a proven way to efficiently generate glycolipid-peptide conjugate vaccines. ,, Conditions promoting oxime bond formation include the use of aniline catalysts under mildly acidic conditions (∼pH 3–5) . To investigate this ligation approach, the corresponding G0 vaccine construct was synthesized whereby α-GalCer amine 5 was reacted with the activated ester of 8-oxo-nonanoic acid ( 23 ) to give α-GalCer ketone 24 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxime ligation between carbonyl-containing compounds (i.e., aldehydes or ketones) and peptides functionalized with an aminooxy group is a proven way to efficiently generate glycolipid-peptide conjugate vaccines. ,, Conditions promoting oxime bond formation include the use of aniline catalysts under mildly acidic conditions (∼pH 3–5) . To investigate this ligation approach, the corresponding G0 vaccine construct was synthesized whereby α-GalCer amine 5 was reacted with the activated ester of 8-oxo-nonanoic acid ( 23 ) to give α-GalCer ketone 24 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate this ligation approach, the corresponding G0 vaccine construct was synthesized whereby α-GalCer amine 5 was reacted with the activated ester of 8-oxo-nonanoic acid ( 23 ) to give α-GalCer ketone 24 (Scheme ). Having previously shown that a solution of aniline and TFA in hexafluoroisopropanol (HFIP) can efficiently catalyze the oxime ligation of an appropriately functionalized glycolipid and peptide, these reaction conditions were examined for synthesis of the G0 vaccine (Scheme ). Starting with ketone 24 and aminooxy acetyl (AoA)-FFRKRAHYNIVTF ( 25 ), a series of concentrations of aniline (100, 200, and 400 mM) in HFIP were assessed for the synthesis of the G0 1:1 conjugate ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the use of synthetic peptides chemically conjugated to immunostimulating lipids, such as a prodrug form of α-GalCer or its derivatives, showed the promising potential of the combined use of iNKT and T cell antigens to increase immune responses in different pathological conditions such as malaria [ 44 ], allergies [ 45 ], and hematopoietic [ 46 ] and solid tumors [ 20 , 47 ]. Moreover, α-GalCer-peptide administration further demonstrated the efficacy of the simultaneous co-delivery of iNKT and T cell antigens compared to the use of free α-GalCer, suggesting the importance of releasing both components within the same antigen-presenting cell, for the iNKT-mediated stimulation of antigen-specific T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The OH at C-6 of the galactose is the only hydroxyl group not involved in hydrogen bonding in the ternary complex between the glycolipid, the CD1d protein and the T-cell receptor (TCR) of iNKT cells, [22] thus it has been the most common site chosen for functionalization en route to immunogenic α-GalCer conjugates. [19,20,23] Herein we open a new diversification hot-spot at a position that has not been previously derivatized, namely the amide bond connecting the phytosphingosine base and the fatty acid. For this purpose, we introduce a multicomponent reaction (MCR) approach that enables the onepot construction of a parallel library of α-GalCer derivatives featuring two different diversification sites.…”
Section: Introductionmentioning
confidence: 99%